A Cyclized Helix‐Loop‐Helix Peptide as a Molecular Scaffold for the Design of Inhibitors of Intracellular Protein–Protein Interactions by Epitope and Arginine Grafting. (28th July 2016) - Fujiwara, Daisuke; Kitada, Hidekazu; Oguri, Masahiro; Nishihara, Toshio; Michigami, Masataka; Shiraishi, Kazunori; Yuba, Eiji; Nakase, Ikuhiko; Im, Haeri; Cho, Sunhee; Joung, Jong Young; Kodama, Seiji; et al.
Abstract: The design of inhibitors of intracellular protein–protein interactions (PPIs) remains a challenge in chemical biology and drug discovery. We propose a cyclized helix‐loop‐helix (cHLH) peptide as a scaffold for generating cell‐permeable PPI inhibitors through bifunctional grafting: epitope grafting to provide binding activity, and arginine grafting to endow cell‐permeability. To inhibit p53–HDM2 interactions, the p53 epitope was grafted onto the C‐terminal helix and six Arg residues were grafted onto another helix. The designed peptide cHLHp53‐R showed high inhibitory activity for this interaction, and computational analysis suggested a binding mode for HDM2. Confocal microscopy of cells treated with fluorescently labeled cHLHp53‐R revealed cell membrane penetration and cytosolic localization. The peptide inhibited the growth of HCT116 and LnCap cancer cells. This strategy of bifunctional grafting onto a well‐structured peptide scaffold could facilitate the generation of inhibitors for intracellular PPIs.